Pharmaceutical Study of Malhara Kalpna Composed of Aloe Barbadensis and Terminalia Belerica - Kumar, Ravinder; Shivani; Katoch, Raghav; Sharma, Shruti; Thamman, Rakesh (International Research Journal of Ayurveda & Yoga, 2022)
The pharmaceutical branch of Ayurveda known as Bhaisajya Kalpana Vigyan deals with the preparation of herbal and herbo-mineral formulations. Numerous infectious diseases in humans are brought on by microorganisms, which are found everywhere in the soil, water, and air. These microorganisms include bacteria, viruses, fungus, and parasites. Our Acharyas have often mentioned Malaharayogas as a way to prevent issues like this. Malhar kalpana falls under the category of Bahya kalpana (external application). Compared to the other formulations, Malhar has a longer shelf element of Malhar. The second is a Dravya known as a pachan Dravya, or a Dravya that turns medications into Malhar such as shatdhaut grit, Sikta tail, Sikta, raal, til oil, etc. The gel of Aloe and the pharmaceutical powder of Baheda are used in making Malhar formulation, resembling ointments used in contemporary pharmaceutics. In this research, an attempt was made to prepare Malhara for exploring the properties of baheda and aloe vera together in semisolid dosage form.